A comparative study on the stability tendencies of balance of power systems : bipolar and multipolar systems - Erdoğan, Özgür (My University, 1996)
unknown
Keywords: Siyasal bilimler (Siyaset bilimi); Toplum bilimleri; Uluslararası ilişkiler; Uluslararası İlişkiler